Design, Manufacture and Characterization of an Acoustic Barrier Made of Multi-Phenomena Cylindrical Scatterers Arranged in a Fractal-Based Geometry - CASTINEIRA-IBANEZ, Sergio; RUBIO, Constanza; ROMERO- GARCIA, Vicent; SANCHEZ-PEREZ, Juan Vicente; GARCIA-RAFFI, Luıs Miguel (Archives of Acoustics, 2012)
In this work we present the design and the manufacturing processes, as well as the acoustics standard-ization tests, of an acoustic barrier formed by a set of multi-phenomena cylindrical scatterers. Periodicarrangements of acoustic scatterers embedded in a fluid medium with different physical properties areusually called Sonic Crystals. The multiple scattering of waves inside these structures leads to attenuationbands related to the periodicity of the structure by means of Bragg scattering. In order to design theacoustic barrier, two strategies have been used: First, the arrangement of scatterers is based on fractalgeometries to maximize the Bragg scattering; second, multi-phenomena scatterers with several noise con-trol mechanisms, as resonances or absorption, are designed and used to construct the periodic array. Theacoustic barrier reported in this work provides a high technological solution in the field of noise control.